Evaluation of genistein ability to modulate CTGF mRNA/protein expression, genes expression of TGFβ isoforms and expression of selected genes regulating cell cycle in keloid fibroblasts in vitro - Jurzak, Magdalena; Adamczyk, Katarzyna; Antończak, Paweł; Garncarczyk, Agnieszka; Kuśmierz, Dariusz; Latocha, Małgorzata (Acta Poloniae pharmaceutica, 2014)
Keloids are characterized by overgrowth of connective tissue in the skin that arises as a consequence of abnormal wound healing. Normal wound healing is regulated by a complex set of interactions within a network of profibrotic and antifibrotic cytokines that regulate new extracellular matrix (ECM) synthesis and remodeling. These proteins include transforming growth factor β (TGFβ) isoforms and connective tissue growth factor (CTGF). TGFβ1 stimulates fibroblasts to synthesize and contract ECM and acts as a central mediator of profibrotic response. CTGF is induced by TGFβ1 and is considered a downstream mediator of TGFβ1action in fibroblasts. CTGF plays a crucial role in keloid pathogenesis by promoting prolonged collagen synthesis and deposition and as a consequence sustained fibrotic response. During keloids formation, besides imbalanced ECM synthesis and degradation, fibroblast proliferation and it's resistance to apoptosis is observed. Key genes that may play a role in keloid formation and growth involve: suppressor gene p53.,cyclin-depend- ent kinase inhibitor CDKN1A (p21) and BCL2 family genes: antiapoptotic BCL-2 and proapoptotic BAX. Genistein (4',5,7-trihydroxyisoflavone) exhibits multidirectional biological action. The concentration of genistein is relatively high in soybean. Genistein has been shown as effective antioxidant and chemopreventive agent. Genistein can bind to estrogen receptors (ERs) and modulate estrogen action due to its structure similarity to human estrogens. Genistein also inhibits transcription factors NFκB. Akt and AP-l signaling pathways, that are important for cytokines expression and cell proliferation, differentiation, survival and apoptosis. The aim of the study was to investigate genistein as a potential inhibitor of CTGF and TGFβ1, β2 and β3 isoforms expression and a potential regulator of p53. CDKN1A(p21), BAX and BCL-2 expression in normal fibroblasts and fibroblasts derived from keloids cultured in vitro. Real time RT-QPCR was used to estimate transcription level of selected genes in normal and keloid fibroblasts treated with genistein. Secreted/cell-associated CTGF protein was evaluated in cell growth's medium by ELISA. Total protein quantification was evaluated by fluorimetric assay in cells llsates (Quant-iT TM Protein Assay Kit). It was found that TGFβ1, β2 and β3 genes expression are decreased by genistein. Genistein suppresses the expression of CTGF mRNA and CTGF protein in a concentration dependent manner, p53 and p21 genes expression are modulated by genistein in concentration dependent manner. The agent also modulates BAX/BCL-2 ratio in examined cells in vitro.